At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Which equation is equivalent to the given equation?

-4(x-5) + 8x = 9x - 3

A. 5x = 17
B. 5x = -12
C. -5x = 2
D. -5x = -23


Sagot :

Sure, let's solve the equation step-by-step.

Given equation:
[tex]\[ -4(x - 5) + 8x = 9x - 3 \][/tex]

First, distribute the [tex]\(-4\)[/tex] through the expression inside the parentheses:
[tex]\[ -4 \cdot x - 4 \cdot (-5) + 8x = 9x - 3 \][/tex]
[tex]\[ -4x + 20 + 8x = 9x - 3 \][/tex]

Next, combine like terms on the left side ([tex]\(-4x + 8x\)[/tex]):
[tex]\[ 4x + 20 = 9x - 3 \][/tex]

Now, to isolate the variable terms on one side, subtract [tex]\(9x\)[/tex] from both sides:
[tex]\[ 4x - 9x + 20 = -3 \][/tex]
[tex]\[ -5x + 20 = -3 \][/tex]

Next, move the constant term ([tex]\(20\)[/tex]) to the right side by subtracting [tex]\(20\)[/tex] from both sides:
[tex]\[ -5x = -3 - 20 \][/tex]
[tex]\[ -5x = -23 \][/tex]

So, the equation equivalent to the given one is:
[tex]\[ -5x = -23 \][/tex]

Thus, the correct answer is:
[tex]\[ \boxed{D. -5x = -23} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.